The Development of Agent Information for Intrusion Detection - Bambang Sugiantoro (Query: Journal of Information Systems, 2017)
As the challenges and problems surround intrusion rises rapidly, the intrusion detection system has been gradually developed. Agent-based approach for intrusion detection system has developed from single to multi agent, and later developed mobile agents in order to increase system's capability to face with a more complex challenge and change. A number of studies had been identified that mobile agent can reduce network traffic, however the study related to intrusion detection using static and mobile agent for finding intruder has not been fully achieved.Keywords:  Information, Intrusion, mobile, networks